KH2PO4 improves cellulase production of Irpex lacteus and Pycnoporus sanguineus - Rodríguez, María Daniela (2018)
The optimization of cellulase production by Irpex lacteus and Pycnoporus sanguineus was investigated. Fractional factorial design was conducted to determine significant variables and interactions. Response surface methodology was applied through Box-Behnken design to determine the optimum level of each factor on cellulase production. The optimal conditions of culture media were (g/L): for I. lacteus CaCl2.2(H2O) 0.3, MgSO4.7(H2O) 0.3 and KH2PO4 3, while for P. sanguineus was CaCl2.2(H2O) 0.1, MgSO4.7(H2O) 0.2 and KH2PO4 9. This optimized medium improved cellulase production, especially β-glucosidase activity values for I. lacteus. KH2PO4 was found in this work to be a useful mineral compound for cellulolytic production.